SYURA DAN LEGITIMASI UMAT DALAM SUKSESI KEPEMIMPINAN KHULAFAUR RASYIDIN - Randy Atma R. Massi (Program Studi Hukum Tata Negara Islam, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2020)
In tracing history, the first problem that was questioned after the death of Muhammad Rasulullah was the problem of political power or his successor who would lead the ummah, commonly known as the caliph. The Qur'an as the main source of reference and the Sunnah does not provide a clear and clear explanation of who has the right to continue the leadership of the ummah after Muhammad's death, and how the succession system or method of appointing leaders in selecting the successor of the Prophet's caliph. So it is not surprising that in the course of the succession system in the appointment of the successor of the Prophet, especially in the appointment of Khulafaur Rasyidin, there were always differences in the ways between one caliph and another. In the matter of leadership succession, the issue of deliberation or shura and the legitimacy of the people or the people does not really get more attention and a significant pressure point, if it is traced in more detail, the issue of shura and the legitimacy of the people or people are two things that always exist in every succession of Khulafaur Rasyidin's leadership. So it is very important in discussing the succession of Khulafaur Rasyidin's leadership in relation to issues of deliberation or shura and the legitimacy of the people. Abstrak Dalam penelusuran terhadap sejarah, permasalahan pertama yang dipersoalkan setelah wafatnya Muhammad Rasulullah adalah masalah kekuasaan politik atau pengganti beliau yang akan memimpin umat, yang lazim disebut dengan khalifah. Al-Qur’an sebagai sumber acuan utama dan Sunnah tidak memberikan penjelasan secara terang dan jelas tentang siapa yang berhak untuk melanjutkan kepemimpinan umat pasca wafatnya Muhammad, dan bagaimana sistem suksesi atau metode pengangkatan pemimpin dalam melakukan pemilihan terhadap khalifah pengganti Rasul. Sehingga tidak mengherankan dalam perjalannya sistem suksesi dalam pengangkatan khalifah pengganti Rasul terutama dalam pengangkatan Khulafaur Rasyidin selalu terjadi perbedaan cara antara khalifah yang satu dengan yang lainnya. Dalam persoalan suksesi kepemimpinan persoalan musyawarah atau syura dan legitimasi umat atau rakyat tidak terlalu mendapat perhatian yang lebih dan titik tekan yang signifikan, jika ditelusuri lebih detail persoalan syura dan legitimasi rakyat atau umat merupakan dua hal yang selalu ada dalam setiap suksesi kepemimpinan Khulafaur Rasyidin. Sehingga sangat penting dalam membahas suksesi kepemimpinan Khulafaur Rasyidin dalam kaitannya dengan persoalan musyawarah atau syura dan legitimasi umat.